The great hiccup. (Economist, 2014)
The article focuses on how a coding problem of the cryptocurrency Bitcoin contributed to a loss in value in 2014. Topics include the theft of BItcoin from the Silk Road 2.0 website selling black market goods and services, how the vulnerabilities of Bitcoin were discovered, and the hacking of Bitcoin. A graph is presented showing the price of the electronic currencies Bitcoin and Mt. Gox between 2013 and 2014.